“Notorious abuse,” “traditious ignorance,” and “ambitious incroachment” in seventeenth-century Dutch, English, and French maps of North America - Petto, Christine M. (Cartographica: The International Journal for Geographic Information and Geovisualization, 2018)
In consideration of Richard Daniel’s alarmed discourse found in the text accompanying his map of the English empire in America (1679), one must investigate the supposedly offending French, English, and Dutch maps of the second half of the seventeenth century for North America and, in particular, the region of the Atlantic coastline and the rhetorical devices of possession found on or in these geographical works. In addition to looking at territorial boundaries, one should also make note of armorial bearings, ships with naval ensigns, toponyms and their placement on the territory, dedicatory cartouches, legends with geographical or historical information, native scenes, and symbols for settlement. In addition to attention to possible constraints on or from the map trade, one must consider the correspondence between colonial officials and their respective governments regarding boundaries, encroachment, sovereignty, or the need for maps with a particular focus on the North American coastline. This correspondence reflects the state’s point of view, which in turn was often manifested on maps and in geographical works. Interestingly intertwined with this outspoken sense of rightful possession were the contemporary claims from some quarters that the cartographic enterprise of the late seventeenth century now embraced an empirical approach, as well as the seemingly opposing thread of the economic realities of the print trade, which often used old copper plates with little to no cartographic revision, so that long after political, economic, or military actions resulted in an “adjustment” in possession, printed maps, atlases, and other geographical works still reflected earlier circumstances. © University of Toronto Press
Keywords: Cartography; Colonies; England; France; History; Netherlands; New England; New Netherland; North America; Seventeenth-century maps; The Netherlands; United Kingdom; colonialism; dept.his; economic history; empirical analysis; historical cartography; human settlement; peer-reviewed; seventeenth century; territorial dispute

A biography of a map in motion: Augustine Herrman's Chesapeake. - Petto, Christine M. (Journal of British Studies, 2019)
Keywords: book.review; dept.his

Map worlds: A history of women in cartography. by will c. van den hoonard - Petto, Christine M (Imago Mundi, 2014)
Keywords: dept.his

Mapping and Charting in Early Modern England and France: Power, Patronage, and Production - Petto, Christine Marie (Toposophia, 2015)
Keywords: Cartography; England; France; History; History; Cartography; History; Map industry and trade; Paris; dept.his; faculty_collection

The Lion and the Lily: Map and Atlas Production in Early Modern England and France. - Petto, Christine Marie (2011)
Dr. Petto completed chapters 2 and 3 and a book proposal for her second manuscript, The lion and the lily: map and atlas production in early modern England and France. Chapter 2 describes local mapping and hydrographic charting initiatives in the 17th and 18th century; chapter 3 focuses on scientific cartography and the efforts of both crowns to map colonial interests in the Americas and Asia. She obtained book contract with Lexington Books, with release date of July 2013.
Keywords: dept.his; faculty_collection; sabbatical_report